Incremental Design of Conceptual Database Schemata with CADDY - Löhr-Richter, Perdita; Engels, Gregor

Bifurcations in Dynamic Systems with Dry Friction - Stelter, Peter; Sextro, Walter (Bifurcation and Chaos: Analysis, Algorithms, Applications)
Dry friction is a main factor of self-sustained oscillations in dynamic systems. The mathematical modelling of dry friction forces result in strong nonlinear equations of motion. The bifurcation behaviour of a deterministic system has been investigated by the bifurcation theory. The stability of stationary solutions has been analyzed by the eigenvalues of the Jacobian. Period doublings and Hopf-bifurcations as well as turning points could be determined with the program package BIFPACK. Phase plane plots of periodic and chaotic motions have been shown for a better understanding of the bifurcation diagrams. Both, unstable branches and stable coexisting solutions have been calculated. Several jumping effects, which are typical for nonlinear systems, have been found.

Visualization in the Analysis Cycle of Observational Data, in Analyzing and Modeling Data and Knowledge - Domik, Gitta; Mickus, KD (Proceedings of the 15th Annual Conference of the "Gesellschaft für Klassifikation e.V." University of Salzburg)

Ernst Schröder und die ,pasigraphischen Systeme‘ von Peano und Peirce - Peckhaus, Volker (Modern Logic)
Modern Logic 1 (1990–91), H. 2/3 (Winter 1990/91) Abstract: Historia Mathematica 18 (1991), #18.4.67 (I. Anellis). Rezensionen: Studia Logica 51 (1992), 150–151 (R. Murawski); MR 92e:03002 (I. Angelelli); Zbl. Math. 735.01007 (I. Grattan-Guinness).

Logic in Transition: The Logical Calculi of Hilbert (1905) and Zermelo (1908) [Abstract] - Peckhaus, Volker (Abstracts of the 9th International Congress of Logic, Methodology and Philosophy of Science, Uppsala, August 7–14, 1991, Bd. 2: General Philosophy of Science. Sections 6–9)

Contract-Oriented System Design and Specification - Müller, Wolfgang (Proceedings of the Workshop on Practical Computer Based Systems Engineering - its Scope and Methods)

Validation of EXPRESS Models Using Prolog - Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1st EXPRESS User's Group Conference)

Letzter Sonntag nach Epiphanias; Predigttext: 2. Korinther 4,6-10 - Schroeter-Wittke, Harald (Gottesdienstpraxis. Serie A. II. Perikopenreihe Band 1)

Application and implementation of neural networks in microelectronics - Goser, K.; Hilleringmann, Ulrich; Rückert, U. (Artificial Neural Networks)
The paper gives an overview on some of the most important artificial neural networks and their implementation as integrated circuits. The performances of these networks are dicussed with regard to the potential of current and future technologies. The overview closes with some possible applications of neural networks in microelectronics.

Maximilian von Löwenthal - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 7)

Approximation of convex polygons - Alt, Helmut; Blömer, Johannes; Wagener, Hubert (Automata, Languages and Programming)

Hilbertprogramm und Kritische Philosophie. Das Göttinger Modell interdisziplinärer Zusammenarbeit zwischen Mathematik und Philosophie - Peckhaus, Volker
Anzeigen: Rundbrief der Philosophisch-Politischen Akademie e.V., Januar 1991); L'Enseignement Mathématique 37 (1991), Nr. 1–2 (Januar–Juni 1991), 5; Das gute Buch in der Schule 1991, Folge 3, 82. Abstract: Historia Mathematica 24 (1997), 230f., #24.2.141 (H.G. Steiner). Rezensionen: History and Philosophy of Logic 12 (1991), 246–247 (Ivor Grattan-Guinness) [zusammen mit M.-M. Toepell, Über die Entstehung von David Hilberts „Grundlagen der Geometrie“, Göttingen 1986]; Studia Logica 50 (1991), H. 2 (Juni 1991), 352–354 (Roman Murawski); Mathesis 7 (1991), 547-549 (J. Padilla Gálvez); Zbl. Math. 715 (Sept. 1991), #715.01018 (R. Rashed); Modern Logic 2 (1991/92), 196–199 (C. Smoryński); Deutsche Zeitschrift für Philosophie 40 (1992), H. 1/2, 191–195 (S. Gottwald); Deutsche Literaturzeitung 113 (1992), 306–308 (S. Paul); MR 92g:01054 (E. Mendelson); Anuario Filosofico 25 (1992), 435–436 (Carlos O. Landázuri); Jahresbericht der Deutschen Mathematiker-Vereinigung 94 (1992), H. 4 (Oktober 1992), 2. Abt., 55 (K. Jacobs); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin 28 (1991/92), H. 2, 290 (R. Tobies); Isis 84 (1993), 823 (H. Mehrtens); Gerhard Heinzmann, « Métamathématique et philosophie », in: L'âge de la science, Bd. 5: Philosophie de la logique et philosophie du langage, Tl. 2, Édition Odile Jacob: Paris 1993, 169–177; Herbert Hrachovez, „Deutsche Positionen zur Informationstechnologie“, Philosophische Rundschau 41 (1994), 300– 314 (Sammelrezension, darin bes. 301–304); „Volker Peckhaus (1990): Los presupuestos intuicionistas del formalismo metamatemático de la Escuela de Gotinga a través de Hilbert“, Anuario Filosófico 30 (1997), Nr. 1, 296–297 (C. Ortiz de Landázuri); Anuario Filosófico 30 (1997), 741–742 (C. Ortiz de Landázuri); D. Rowe, “Perspectives on Hilbert”, Perspectives on Science 5 (1997), 533–570 (Sammelrezension, darin bes. 546– 553); Revue des Sciences philosophiques et théologiques 83 (1999), 141–143 (J. Courcier).

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 6,1: Briefe 1838-1847. Teil 1: Text (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Formal Semantics of an Entity-Relationship Query Language - Hohenstein, Uwe; Engels, Gregor (Proceedings of the 9th International Conference on Entity-Relationship Approach (ER 90), Lausanne, Switzerland)

The Influence of the Capsulation on the Efficiency of PV-Modules. - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 1st World Renewable Energy Congress, Reading (UK), 23.–28. September 1990, Band 1, S. 141–144.)

Elementary Actions on an Extended Entity-Relationship Database - Engels, Gregor (Proceedings of the workshop on Graph Grammars and Their Application to Computer Science (1990), Bremen (Germany))
Semantic data models have been widely studied for the conceptual specification of databases. However, most of these data models are restricted to the description of the static structure of a database. They do not provide means to specify the dynamic behaviour of a database. This paper sketches a language for the specification of actions on databases which have been specified by an Extended Entity-Relationship (EER) schema. These actions are based on so-called elementary actions, which are automatically be derived from the EER schema. So, it can always be guaranteed that these schema dependent elementary actions preserve all inherent integrity constraints. The semantics of the elementary actions is given in two steps: First, it is shown how the semantics of a database schema, i.e., a current database state, can be represented by an attributed graph. Then, the semantics of elementary actions is given by programmed graph replacements.

A new universal class of hash functions and dynamic hashing in real time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Automata, Languages and Programming)

Dynamic hashing strategies - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the complexity of genuinely polynomial computation - Karpinski, Marek; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

How to distribute a dictionary in a complete network - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)